SAT0020 The citrullinome in tissue and biofluids of human and mouse origin. (15th June 2017) - Poulsen, TBG; Damgaard, D; Bennike, TB; Meyer, MK; Elbæk, KJ; Andersen, V; Birkelund, S; Nielsen, CH; Stensballe, A
Abstract : Background: Protein citrullination is fundamental to several essential processes in apoptosis and antimicrobial defense, however, also linked to multiple pathogenic endpoints. This post-translational modification (PTM), by conversion of arginine to citrulline residues, is mediated by peptidylarginine deiminase (PAD) enzymes found in specific cells and tissues. In polymorphonuclear cells (PMNs) these enzymes enable NETosis, a specialized form of programmed necrosis and the formation of NETs (neutrophil extracellular traps). Also, these enzymes are expressed in the synovium of patients with rheumatoid arthritis (RA) thereby triggering the production of autoantibodies against citrullinated proteins (ACPAs). Objectives: Our objective was to optimize methodology for characterization of this PTM and determine the citrullinome in tissue and biofluids of human and mouse origin in clinical relation to rheumatoid arthritis (RA), osteoarthritis (OA), Spondyloarthritis (SpA) as well as presence of ACAPs and NETs Methods: Synovial fluid (SF) and plasma was collected from patients diagnosed with RA, OA, SpA (n=120). Inflammation levels patients were characterized with plasma C-reactive protein (CRP), and circulating anti-CCP levels as well as 10 most relevant proinflammatory cytokines. Intestinal tissue (colon mucosa) from RA patients (n=10) and joint lysate from collagen-induced arthritis mouse model (n=24). All samples were analyzed by citrulline specific sample preparation and high-end mass spectrometric analysis [1, 2]. Follow-up studies were performed by multiple techniques including confocal microscopy and cell-free DNA measurement. Results: The proteome analysis of SF allowed deepest proteome analysis so far (Proteoforms >1300) as well as a number of citrullinated sites. The three patient groups could be differentiated by cluster analysis and the occupancy of each modified site calculated. The investigation of the intestinal tissue enabled identification of 223 citrullinated peptides from 121 proteins. Three of the peptides were unique to RA. The list of citrullinated proteins was enriched in extracellular and membrane proteins and included known targets of anticitrullinated protein antibodies (ACPAs). Investigation of collagen-induced arthritis mouse model enabled differential analysis of the proteome as response to treatment and determination of the PTMs associated with this model. Conclusions: Our deep proteome based analysis of tissue and biofluids have enabled an extended catalogue of citrullinated proteins and sites relevant to improved disease subtyping as well as a source of citrullinated sites for future studies. References: Bennike, T.B., Ellingsen, T., Glerup, H., Bonderup, O.K., Carlsen, T.G., Meyer, M.K., Bøgsted, M., Christiansen, G., Birkelund, S., Andersen, V., et al. (2017). Proteome Analysis of Rheumatoid Arthritis Gut Mucosa. J. Proteome Res. 16, 346–354. Tue Bennike, Kasper B. Lauridsen, Michael Kruse Olesen, Vibeke Andersen, Svend Birkelund and Allan Stensballe (2013). Optimizing the Identification of Citrullinated Peptides by Mass Spectrometry: Utilizing the Inability of Trypsin to Cleave after Citrullinated Amino Acids. Journal of Proteomics & Bioinformatics 06. Disclosure of Interest: None declared